Effect of the Addition of Proteins and Hydrocolloids on the Water Mobility in Gluten-Free Pasta Formulations - Larrosa, Virginia Judit (2012)
In a gluten free pasta formulation (suitable for celiac people), the influence of each constituent has a major importance on the final product quality, especially water and hydrocolloids contents used to replace the gluten matrix. The presence of hydrocolloids and proteins in dough may modify the availability of water to interact with starch in the gelatinization process. The aim of the present work was to investigate the effect of the addition proteins and hydrocolloids addition on the water-starch interaction using a triangular mixture design. Basic dough formula consisted in a mixture of corn starch and flour (4:1, 53.5%), 1%NaCl, and 3% sunflower oil, water (35.48-39.5%), gums (xanthan and locust bean gums, 2:1 ratio, 0.512-2.519%), and proteins (dry egg and ovoalbumin mixtures, 10:1 ratio, 0.683-6.704%) Combinations of gums, proteins, and water were used in a simplex-centroid design with constrains. Modulated differential scanning calorimetry was used to study starch gelatinization and the amount of unfrozen water in the samples; thermograms were obtained between -50ºC and 140ºC (heating rate 5ºC/min, modulated at ±1ºC, period of 60s). Regarding the process of gelatinization, a biphasic endotherm was observed; when the free water content of the dough was progressively reduced (0.94 to 0.42g H2O/ g dough), endotherms shifted to higher temperatures (onset from 56.7ºC to 63.1ºC, first peak from 75.1ºC to 77.6ºC) following a linear relationship. The response surface analysis of the unfrozen water content of the complex composite system as a function of the concentration of proteins, hydrocolloids, and water led to a “saddle” type surface, involving interactions between components.